Practical Technique for Cholera Surveillance and Outbreak Investigation - Ardkean, Wanchai (Journal of Health Science of Thailand, 2018)
Cholera is a well-known endemic disease in Thailand. In the past, public health personnel especially provincial epidemiological workers could handle it very well until cholera problem has been relalivety under control. Nowadays emerging infectious diseases, governmental reorganization, and the Surveillance and Rapid Response Team (SRRT) Development Project have tilted the balance and bring about many changes on the scenario relating to the main roles of surveillance and outbreak investigation. The major change is transferring main responsibility from a provincial to a district level. As such, tacit knowledge and skills on cholera practices have declined. Preparing for recurrent cholera outbreak, the new district SRRT needs to strengthen their tacit knowledge and skills on cholera step by step such as; 1) surveillance and outbreak detection 2) active case finding and carriers 3) linking investigation and interpretation to define source of the outbreak 4) collecting specimens 5) containment 6) recommendation for control the epidemic and finally 7) writing an investigation report.